A review of the performance of geosynthetics for environmental protection. Issue 5 (October 2016) - Touze-Foltz, N.; Bannour, H.; Barral, C.; Stoltz, G.
Abstract: This paper, which is based on an Invited Lecture for the 7th International Conference on Environmental Geotechnics, gives an updated overview of the properties of transfer of geosynthetic liner materials used in environmental applications. To begin, the water-retention curves of geosynthetic clay liners (GCLs) are discussed, with the focus being on the high temperatures that can be encountered and the concomitant risk of desiccation. Next, an overview is given of quantifying advective transfer through intact geomembranes (virgin or after exposure on site) and through multicomponent GCLs. Experimental quantification of advective transfer through composite liners is also addressed, whereby geomembranes or the film or coating of a multicomponent GCL is damaged. Finally, based on a literature review including the most recent data, the discussion turns to the diffusion of organic and inorganic species through virgin and aged geomembranes and GCLs. The synopsis of the most recent data presented here in terms of elementary transfer mechanisms, either advective or diffusive, should contribute to improving the quantification of transfer through barrier systems. These four topics were selected as they correspond to the fields of expertise of the co-authors in which they have been publishing in the past 20 years.